2020
DOI: 10.3390/ma13020307
|View full text |Cite
|
Sign up to set email alerts
|

Denture Base Composites: Effect of Surface Modified Nano- and Micro-Particulates on Mechanical Properties of Polymethyl Methacrylate

Abstract: The most commonly used denture base material, polymethyl methacrylate, lacks ideal mechanical properties, which are reflected in its relatively high failure rate. Several methods have been explored to reinforce the material and reduce the cost of denture repair and replacement. In this study, various surface modified filler particles at different concentrations were dispersed in conventional and high-impact denture base materials and tested for their improvement in mechanical properties. Inorganic filler parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…At the highest concentration, the E-glass fillers had increased the hardness of the composites by the highest amount followed by the ZrO 2 and then the TiO 2 . This result is in agreement with previous research, which has found that the addition of glass fibre [9,36], ZrO 2 [5,18] and TiO 2 [12,15] nanoparticles in PMMA at different concentrations statistically improved the surface hardness of PMMA denture bases. The increase in filler content enhanced the surface hardness up to the point at which the optimal level was achieved [22].…”
Section: Discussionsupporting
confidence: 93%
“…At the highest concentration, the E-glass fillers had increased the hardness of the composites by the highest amount followed by the ZrO 2 and then the TiO 2 . This result is in agreement with previous research, which has found that the addition of glass fibre [9,36], ZrO 2 [5,18] and TiO 2 [12,15] nanoparticles in PMMA at different concentrations statistically improved the surface hardness of PMMA denture bases. The increase in filler content enhanced the surface hardness up to the point at which the optimal level was achieved [22].…”
Section: Discussionsupporting
confidence: 93%
“…The reduced interactive contact points between chitosan and heat polymerized denture base resin in higher concentrations lead to poor adhesion and easy detachment from the resin matrix leading to voids and reduce the mechanical properties of the newer composite material. Asar et al [11], Nejatian T et al [40], Shakeri et al [41] observed the findings of the reduced interactive contact points in higher concentrations of different composite materials.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, PMMA absorbs water, which may compromise its physical and mechanical properties while in use [ 63 , 64 ] and make it vulnerable to failure under cyclic loading [ 65 ]. Currently, a number of researchers are focused on mechanical reinforcement [ 30 , 38 , 51 , 53 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and chemical modification [ 53 , 75 , 76 ] of PMMA to overcome its drawbacks and improve its properties, which have been reviewed in this article. In order to better understand and interpret these recent modifications, it is important to understand the chemistry, types, and properties of PMMA materials.…”
Section: Historical Background and Developmentmentioning
confidence: 99%
“…The PMMA-based materials should have certain desired properties depending on the biological application. Accordingly, PMMA materials have been extensively modified and explored in relation to various chemical [ 77 , 99 ], biological [ 77 , 100 , 101 , 102 ], physical [ 70 , 77 , 103 ], and mechanical properties [ 66 , 68 , 70 , 100 , 103 , 104 , 105 ]. Primarily, it is important to understand the ideal or desired properties of PMMA materials for denture base applications ( Figure 3 ).…”
Section: Properties Of Pmmamentioning
confidence: 99%
See 1 more Smart Citation